Evaluation of Glutaminolysis in T Cells. Issue 9 (16th September 2022) - Tajima, Masaki; Strober, Warren
Abstract: The activity of living cells is necessarily dependent on the amount of available bioenergy. In T cells, the latter is mainly derived from ATP, a molecular energy "coin" generated by one of several metabolic processes that differ in their ability to satisfy energy demand. Thus, whereas naïve or quiescent T cells efficiently utilize oxidative phosphorylation to generate ATP, T cells subjected to antigenic stimulation followed by clonal expansion and cytokine production meet their increased need for energy by supplementing ATP generation by oxidative phosphorylation with ATP generation by glycolysis. Yet additional need for ATP can be met by other basic biologic sources of energy such as glutamine, an amino acid that is metabolized through a process called glutaminolysis to result in end products that flows into the TCA cycle and augment ATP generation by oxidative phosphorylation. It is now possible to track the dominant energy supplying processes (i.e., the ATP generation process) in differentiating or activated T cells in a real‐time manner. Here, we provide one element of such tracking by describing protocols for the assessment of the contribution of glutaminolysis to overall ATP production within different T cell subsets. © 2022 Wiley Periodicals LLC. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Basic Protocol 1 : Evaluation of the role of glutaminolysis during T cell activation/differentiation Basic Protocol 2 : Evaluation of the role of glutaminolysis in T cell responses utilizing glutaminolysis inhibitors Basic Protocol 3 : Evaluation of the effect of glutaminolysis on cellular oxidative phosphorylation/glycolysis